Journal of Event, Tourism and Hospitality Studies (JETH) 2021
DOI: 10.32890/jeth2021.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Tourists’ Food and Beverage Needs and Preferences During Travel

Abstract: The Muslim travel market is regarded as an encouraging market in the tourism industry at the current state. Muslim tourists prefer to select a tourist destination whereby Islamic elements are available, which permits them to enjoy their travels without neglecting the religious obligations. These elements undoubtedly will provide an enriching experience during their travels. Therefore, this paper aims to examine experiences faced by Muslim tourists in terms of their needs and preferences in the provision of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The qualitative research method, i.e. in-depth interview, is appropriate for this research, which could be supported by several studies in the food tourism domain (Fusté-Forné, 2023) and on the topic of halal food and tourism (Zainol et al , 2021; Mannaa, 2019). Additionally, since the concept is relatively new in the context of China, Xiong and Zhang (2020, 2021) also adopted in-depth interviews and thematic analysis to explore halal tourism and halal food in China.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative research method, i.e. in-depth interview, is appropriate for this research, which could be supported by several studies in the food tourism domain (Fusté-Forné, 2023) and on the topic of halal food and tourism (Zainol et al , 2021; Mannaa, 2019). Additionally, since the concept is relatively new in the context of China, Xiong and Zhang (2020, 2021) also adopted in-depth interviews and thematic analysis to explore halal tourism and halal food in China.…”
Section: Methodsmentioning
confidence: 99%
“…The availability of halal food will also influence Muslim tourists’ length of stay and type of accommodation chosen (Mannaa, 2019). Zainol et al (2021) found that it is difficult for Muslim tourists to find halal food in non-Muslim countries and identified three themes of Muslim tourists’ needs and preferences in the provision of food and beverage services during travel: the convenience of finding halal outlets or halal food, the restaurants/outlets with certified halal logo and the experience regarding different food culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By attracting more Muslim travellers, Muslim-friendly homestays can contribute to the overall growth of the tourism industry and bring in additional revenue for local communities (Ibrahim, 2013; Muslim et al , 2004). Muslim-friendly homestays may encourage openness and tolerance by providing a welcoming and accommodating atmosphere for visitors from various cultures (Zainol et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A “Muslim-friendly” homestay is a type of accommodation designed to cater to the needs and preferences of Muslim travellers (Bangsawan et al , 2019; Muin et al , 2022). Such homestays typically provide amenities and services that align with Islamic practices and beliefs, such as prayer mats, Qurans and halal food options (Zainol et al , 2021). They may also have separate prayer rooms or areas for performing ablutions (wudu) and segregated swimming pools and recreational facilities for men and women (Bangsawan et al , 2019; Rashidi et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the demand for halal food is also requested by Muslims and non-Muslims worldwide [7]. Muslim tourist consideration when deciding to go to a restaurant is the existence of the Halal logo [8]. To obtain a halal logo, businesses need to pay attention to the entire SC of the products.…”
Section: Introductionmentioning
confidence: 99%